Prevalence, risk factors and first record of mitochondrial cox1 gene-based molecular characterization of Paramphistomum epiclitum from Pakistan - Alvi, Mughees Aizaz; Alshammari, Ayed; Asghar, Faizan; Ali, Rana Muhammad Athar; Li, Li; Saqib, Muhammad; Khan, Muhammad Kasib; Imran, Muhammad; Qamar, Warda; Askar, Hussam; Abdelsater, Naser; Fu, Bao-Quan; et al. (Frontiers in Veterinary Science, 2022)
Parasitic infestations are one of the major threats to the livestock industry in Pakistan. These have a negative impact on the production of domesticated livestock species. Paramphistomes belong to the superfamily Paramphistomoidea and are involved in infecting ruminants all over the world. To date, there was no information on mitochondrial DNA-based molecular characterization of Paramphistomum epiclitum from Pakistan. To close this research gap, this study was designed to provide insights into the epidemiology of Paramphistomum species. Paramphistomum epiclitum isolates were recovered from the rumen of small ruminants slaughtered at an abattoir located in Faisalabad city and animal demographics were recorded. DNA was extracted and mitochondrial cox1 was amplified and sequenced. Prevalence was calculated along with a 95% confidence interval in various groups. The Chi-square test was applied to determine the association between different variables under investigation. A phylogenetic tree was constructed based on the Bayesian method. Population diversity indices were calculated using DnaSP 4.5 software. A total of 43 mutations were observed among 7 haplotypes. Negative values of Fu’s Fs values, and Tajima’s D indicated population expansion. Deworming, season and grazing were the variables that significantly correlate (p<0.05) with the prevalence of P. epiclitum. The high prevalence of P. epiclitum demonstrates that more studies are indeed needed to further understand the prevalence and distribution of P. epiclitum in definitive and all potential intermediate hosts in addition to intraspecies variation and relationship with populations from other locations.